Colley Cibber : A Biography - Koon, Helene, 1925-1996 (Book collections on Project MUSE., 2015)
Colley Cibber changed the course of the English-speaking theater. One of the most complete theater men in the history of the stage, he fostered the change from drama as the handmaiden of literature to theater as an independent and lively art. In the process, Cibber became one of London's brightest stars, one of its most popular playwrights and, for thirty years, manager of the most important theater in England, Drury Lane. Yet above all, Cibber was an actor, and this fact governed his life and career. In his plays, he demonstrated a remarkable awareness of the audience in the playhouse, while t.